1996
DOI: 10.1210/en.137.8.3163
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-stimulating hormone inhibits Fas antigen-mediated apoptosis of human thyrocytes in vitro

Abstract: The mechanisms of TSH-induced growth stimulation of thyrocytes in vivo have yet to be elucidated. We examined the antiapoptotic effect of TSH toward Fas antigen-mediated apoptosis of thyrocytes. Fas antigen was expressed on approximately 40% of unstimulated thyrocytes, and the expression was significantly inhibited by the addition of TSH in a dose-dependent manner. Treatment of thyrocytes with 8-bromo-cAMP mimicked the effect of TSH, suggesting that the inhibitory effect of TSH on Fas antigen expression was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Fas antigen is functionally expressed on the surface of thyrocytes, and TSH inhibits Fas antigen-mediated apoptosis of thyrocytes resulting in the promotion of growth of the thyroid gland [15]. Intercellular adhesion molecule-1 and class II MHC have been implicated as contributing factors for numerous diseases, including autoimmune thyroid diseases, and TSH could downregulate their interferon-γ-mediated expression [16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Fas antigen is functionally expressed on the surface of thyrocytes, and TSH inhibits Fas antigen-mediated apoptosis of thyrocytes resulting in the promotion of growth of the thyroid gland [15]. Intercellular adhesion molecule-1 and class II MHC have been implicated as contributing factors for numerous diseases, including autoimmune thyroid diseases, and TSH could downregulate their interferon-γ-mediated expression [16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In normal circumstances, the Fas pathway is inhibited, whereas in inflammation, it is activated by cytokines [153]. In vitro studies have shown that TSH inhibited Fas-mediated apoptosis, while the absence of TSH induced apoptosis [154]. A combination of IFN-γ with TNF-α or IL-1β stimulated the Fas-activated apoptosis in cultured thyroid follicular cells [155].…”
Section: Thyroid Destructionmentioning
confidence: 99%
“…The decrease in the number of Treg cells (especially CD25+) induced development of lymphocytic infiltrations in the thyroid and hypothyroidism [11]. Thyroid dysfunction is connected with thyrocyte apoptosis in the vicinity of active lymphocytes [12,13,14,15]. Numerous fibroblasts and collagen fibres may be observed in the thyroid tissue in Hashimoto’s thyroiditis.…”
Section: Introductionmentioning
confidence: 99%